ANALISA STRATEGI DIVERSIFIKASI PRODUK UNTUK MENINGKATKAN KEUNGGULAN BERSAING - Rahmandwika, Arfian Rizky; Mulyati, Awin; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2019)
The development of UKM is growing rapidly and one of them developing in Sidoarjo, especially in the convection business at this time the competition is getting tougher, because there have been many of the same businesses, like shoes, bags, clothes and others. To overcome the increasingly fierce competition, a convection business is needed to have a strategy to achieve a competitive advantage through a product diversification strategy. One of the convection businesses that have diversified their products in Sidoarjo is UKM Putra Delta which is in Punggul Sidoarjo Village. Putra Delta UKM to increase its struggle in competing with other convection UKM, namely through various ways of product diversification which strives to be able to continuously compete with other UKM and open an opportunity to expand the Putra Delta UKM business. The purpose of this research is to explain a type, the process of planning and implementation of diversification strategies in Putra Delta UKM. This type of research is descriptive and this research uses a qualitative approach. Its using method of interviews, documentation and observation as collecting data. The results of this study are the product diversification strategy in Putra Delta UKM including concentric diversification strategy where there is a new product development in Putra Delta UKM. Examples of products from UKM Putra Delta themselves are: official hats, school ties, school belts, school badge, hasduk, veils, school uniforms, school exercise shirts, academic certificate folders, and graduation equipment. this strategy properly planned and immediately implemented properly, this strategies has proven to have a good effect on competitive advantage in the Kampung Topi Industrial Center.Keywords: Product Diversification, Competitive Advantage